Kedudukan Hukum Akta Jaminan Fidusia yang ditandatangan oleh Para Pihak Diluar Wilayah Kerja Notaris di Denpasar - Ni Kadek Shonia Virgayanti; Nella Hasibuan O’leary; Ni Made Sukariati Karma (Warmadewa Press, 2022)
Notaries when carrying out their duties must be based on the Law on Notary Positions (UUJN) and the Notary Code of Ethics. This research was carried out with the aim of knowing the implementation of the preparation of the Fiduciary Guarantee Deed (AJF) by a Notary, and finding out the legal position of AJF which is signed by parties outside the Notary's working area. This research is empirical research, problem approach with descriptive research type and juridical-empirical approach. There are several sources, namely primary material sources and secondary material sources. Where the primary material source comes from the legislation related to the research case. While the secondary material comes from the results of interviews that support the primary material as well as relevant legal books. Data collection techniques are interviews and library studies. The results of the research show that AJF is made by a notary when someone appears and asks for the service. AJF is then registered to obtain a Fiduciary Guarantee Certificate. The legal position of the AJF that is compiled is not in the area where the Notary works, that is, the deed acts like an underhand deed. The notary has a dispensation to draw up the deed, not in the vicinity where he works, it is in an open inheritance area.